2019
DOI: 10.1093/eurheartj/ehz746.0087
|View full text |Cite
|
Sign up to set email alerts
|

5937Natural history of functional tricuspid regurgitation: implications of quantitative doppler assessment

Abstract: Objectives To establish the prognostic value of quantitative measures of functional tricuspid regurgitation (TR) severity i.e. effective regurgitant orifice area (EROA) and regurgitant volume. Methods 382 patients with HFrEF on guideline-directed medical therapy were enrolled and TR EROA as well as regurgitant volume by Doppler/2D-echocardiography were assessed. All-cause mortality was defined as the primary study endpoint. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…However, this study was performed on a selected population, predominantly men, and more severe TR was associated with lower LVEF, leaving the intrinsic effect of TR on survival in doubt. Following this seminal paper, several studies also suggested that TR was associated with worse outcomes, 3,6,8,9 while other studies did not find such association 10,11 . Recently, a meta‐analysis from 70 studies encompassing 32 601 patients concluded to an independent association between moderate or severe TR and mortality, 21 but could not eliminate the effect of comorbidities on mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was performed on a selected population, predominantly men, and more severe TR was associated with lower LVEF, leaving the intrinsic effect of TR on survival in doubt. Following this seminal paper, several studies also suggested that TR was associated with worse outcomes, 3,6,8,9 while other studies did not find such association 10,11 . Recently, a meta‐analysis from 70 studies encompassing 32 601 patients concluded to an independent association between moderate or severe TR and mortality, 21 but could not eliminate the effect of comorbidities on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…TR is highly prevalent 5,6 but the impact of TR on survival in patients with HF is disputed. While recent studies suggested a link between TR and worse outcomes, predominantly in the context of severely reduced systolic function, 3,5–9 other studies found no independent association with survival 10,11 . Furthermore, most studies on functional TR have been modest in size, have focused on HF with reduced ejection fraction (HFrEF) and have not considered HF as a global entity inclusive of preserved ejection fraction (HFpEF) and have originated from single tertiary referral centres with inherent referral bias, but also with expert interpretation of TR severity, a notoriously complex evaluation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…42 Moreover, recent publications have shown that the current cut-off values for quantitative parameters used to assess TR severity are inadequate to quantify the burden on the RV and it is likely that lower threshold values of effective regurgitant orifice area (EROA) and regurgitant volume define severe TR. 43 This finding was also supported by the study of Bartko et al 44 showing a significant increase in mortality and morbidity for EROA > _0.2 cm 2 and regurgitant volume > _20 mL in HF patients with reduced ejection fraction. This may potentially impact the therapeutic decision-making, particularly timing for intervention.…”
Section: Imaging For Decision-making In Patients With Tricuspid Regurmentioning
confidence: 53%
“…7 Indeed, TR was also found to be heterogeneous in survival according to its cause 8 and severity. 9 Overall, however, very high mortality…”
Section: Real-time 3d-tee Data Acquisition and Tv Demonstrationmentioning
confidence: 99%